Assessment of Groundwater Quality in Ha Tinh Province Using Water Quality Index - Kien, Truong Trung; Chau, Nguyen Dang Giang; Hop, Nguyen Van; Tung, Truong Quy (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 3DO - 10.25073/2588-1140/vnunst.5845, 2025)
The Groundwater Quality Index (GWQI) was developed and applied to assessment of groundwater quality in Ha Tinh province. This study utilized water quality monitoring data in 2018 - 2020 period at 58 locations with a frequency of 4 times/year in 13 districts, towns and city in the province. Ten (10) parameters were selected (i = 1 - 10) to establish the GWQI, including: pH, total dissolved solids (TDS), hardness (HARD); sulfate (SO4), chemical oxygen demand (COD), ammonium as nitrogen (N-NH4), nitrate as nitrogen (N-NO3), total dissolved iron (Fe), total dissolved manganese (Mn) and total coliform (TC). The weight (w i ) of each parameter was based on principal component analysis (PCA) using monitoring data in 2018 and 2019. The sub-index (q i ) of each parameter was determined by a linear function, based on the limit value ​​specified in the National Technical Regulation on Domestic Water Quality (QCVN 01-1:2018/BYT). The GWQI as a function of w i and q i was calculated by the multiplicate formula. The results showed that in 2020, in the province 21.1% of GWQI values ​​ classified as VERY GOOD or GOOD, 31.9% as AVERAGE, 33.2% as POOR and 13.8% as VERY POOR.